2017
DOI: 10.4103/jiaps.jiaps_5_17
|View full text |Cite
|
Sign up to set email alerts
|

Congenital pouch colon

Abstract: Congenital pouch colon (CPC) is an unusual abnormality in which a pouch-like dilatation of a shortened colon is associated with an anorectal malformation. It is categorized into four subtypes (Types I–IV) based on the length of normal colon proximal to the colonic pouch. In males, the pouch usually terminates in a colovesical fistula just proximal to the bladder neck. In girls, the terminal fistula opens either into the urethra or in the vestibule, close to the urethral opening. Girls usually have a double vag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 37 publications
2
31
0
7
Order By: Relevance
“…[1] In most descriptions, CPC in male children presented with absent anal opening and had communication with the genitourinary tract. [45] In our study also, while the most common presentation was similar to that described in the literature, i.e., absent anal opening and colovesical communication, 15 children presented in a different manner, and consequently, the management was also different.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…[1] In most descriptions, CPC in male children presented with absent anal opening and had communication with the genitourinary tract. [45] In our study also, while the most common presentation was similar to that described in the literature, i.e., absent anal opening and colovesical communication, 15 children presented in a different manner, and consequently, the management was also different.…”
Section: Discussionsupporting
confidence: 83%
“…In males, the pouch usually terminates in a colovesical fistula just proximal to the bladder neck. [14] CPC has been included, as a rare variant, in the Krickenbeck classification of ARM. A recent review showed that about 90% of reported cases in the world were from India.…”
Section: Introductionmentioning
confidence: 99%
“…Sacral agenesis, bilateral vesicoureteric reflux and cyanotic congenital heart diseases were the most common associated congenital anomalies. The mortality rate may reach 10–15% after surgical intervention [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…The association of pouch colon anomaly with VUR has previously been defined in various studies,[ 1 2 ] but the exact incidence is still not known. Associated genitourinary system anomalies were seen in 20/56 patients (35.71%), of which VUR was seen in all six patients who underwent cystourethrogram; in rest of the 50 patients, cystourethrogram was not done.…”
Section: Discussionmentioning
confidence: 99%
“…C ongenital pouch colon (CPC) syndrome is a rare variant of high anorectal malformation in which there is a complete absence of the rectum and variable length of the colon terminating in a dilated pouch that most commonly opens directly into the bladder through a wide fistula. [ 1 ] Based on the length of the colon, there are four types. About 37.46% of patients of CPC have associated genitourinary anomalies, among which vesicoureteric reflux (VUR) accounts for almost 17%.…”
Section: Introductionmentioning
confidence: 99%